2017
DOI: 10.3991/ijet.v12i10.6993
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reflective Teaching Applications Supported by Edmodo on Prospective Teachers’ Self-Directed Learning Skills

Abstract: The purpose of this research is to determine the impact of reflective teaching applications supported by Edmodo on prospective teachers’ self-directed learning skills. Also, the views of prospective teachers’ regarding the use of Edmodo in education, which is a social learning platform, are determined. For the research, both qualitative and quantitative data were collected from 36 prospective teachers within the scope of the “Teaching Practice” course. A 12-week application has been conducted online with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Being in a collaborative environment with their teachers and classmates makes them more active and motivated to participate in learning activities. Edmodo's effectiveness in supporting conventional learning was similar to that found by previous studies, which also observed positive effects on student performance .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Being in a collaborative environment with their teachers and classmates makes them more active and motivated to participate in learning activities. Edmodo's effectiveness in supporting conventional learning was similar to that found by previous studies, which also observed positive effects on student performance .…”
Section: Discussionsupporting
confidence: 87%
“…On the basis of these findings, Edmodo appears to be easy to use, provides a safe working environment, increases lesson participation, communication, and responsibility, and helps in organizing course resources. The students' positive opinions echo those seen by other studies in the literature [3,17,25,37]. The problems the students were confronted with were related to the Edmodo system's technical infrastructure, which is expected to improve over time because of system updates.…”
Section: Discussionsupporting
confidence: 74%
“…Edmodo is a social networking media that is safe for students and teachers who refer to Facebook social networks, so this system has features similar to Facebook. In fact, many say Edmodo is a Facebook school, because besides being a social networking media among its users, Edmodo also supports the online learning process [23]. At this site parents can also join and communicate with teachers and parents or guardians of other students, besides that of course with their own sons or daughters so they can find out the activities and results of their children [24].…”
Section: Edmodomentioning
confidence: 99%
“…Various forms of online learning that often sound like web-based learning [14], [15] as well as application or platform-based learning such as e-learning [16], [17], Google Classroom [18], [19], game quiz [20], and MOOCs [21]- [23]. In addition, widelyknown application or platform-based learning is Edmodo [24]- [26].…”
Section: Introductionmentioning
confidence: 99%